2022
DOI: 10.18502/ijpho.v12i1.8359
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body mass index and serum ferritin level in pediatrics with Beta-thalassemia major disease

Abstract: Background: Beta-thalassemia major is a type of inherited blood disease that results in variable outcomes such as severe anemia due to haemoglobin chains. Recurrent and lifelong blood transfusions as a treatment in beta-thalassemia major disease lead to iron deposition in various organs and cause the failure of multiple organs. Failure of affected organs leads to Body mass index (BMI) abnormality. This study aimed to evaluate the association between BMI and serum ferritin level as a marker for iron overload.&#… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Moreover, there was no significant relationship between gender and BMI in the study ( P value < 0.89 ), along with ours ( P value < 0.177 ). 12 Participants were considered underweight according to The Growth Charts for Saudi Children and Adolescents endorsed by The Health Services Council of Saudi Arabia, where a BMI less than −2 standard deviations was identified as underweight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there was no significant relationship between gender and BMI in the study ( P value < 0.89 ), along with ours ( P value < 0.177 ). 12 Participants were considered underweight according to The Growth Charts for Saudi Children and Adolescents endorsed by The Health Services Council of Saudi Arabia, where a BMI less than −2 standard deviations was identified as underweight.…”
Section: Discussionmentioning
confidence: 99%
“…Journal of Blood Medicine 2022:13 770 among beta thalassemia major patients, as has been reported by several studies. [11][12][13] Chelation therapy has a major role in decreasing or delaying such complications. The findings of this study might help improve the quality of healthcare services provided to these patients by exploring barriers that hinder compliance with chelating therapy.…”
Section: Dovepressmentioning
confidence: 99%
“…This is in line with Yousefian et al's study which examined 740 patients with major-beta thalassemia, where the BMI rate was reported to be lower when compared to controls. [10] Patients with thalassemia are at risk for nutritional deficiencies due to increased nutritional requirements to maintain normal erythropoiesis and/or lack of intake and absorption of nutrients. [11,12] In patients with delayed sexual development or hypogonadism, there may be a development that is not age-appropriate.…”
Section: Correlation Of Leptin Levels With Free Testosterone and Body...mentioning
confidence: 99%
“…However, the mechanism is still unclear. [10] In a study conducted by Ozata et al, it was found that leptin levels were negatively and significantly correlated with testosterone levels in patients with idiopathic hypogonadotropic hypogonadism both before and after therapy.…”
Section: Introductionmentioning
confidence: 96%
“…( 5) Iron overload may result in patients' impaired growth, including inadequate body mass index (BMI) and short stature. (6) Iron accumulation in the pituitary causes hypogonadism and is one of the most frequent complications experienced by TDT patients. It is known that 70-80% of TDT patients who experience hypogonadism may have pubertal failure, sexual dysfunction, and infertility.…”
Section: Bmi Measurementmentioning
confidence: 99%